Polish Literature and National Identity : A Postcolonial Perspective - Skórczewski, Dariusz (Book collections on Project MUSE., 2020)
"Although for half a century East-Central Europe was part of the Soviet empire and was subject to its "civilizing" mission, its colonial status escaped the attention of most postcolonial critics. It still remains a blank spot in global studies of postcolonialism. In Polish Literature and Identity: A Postcolonial Landscape Dariusz Skórczewski argues for the advantages of applying postcolonial thought to Polish realities; at the same time, he modifes the theoretical framework worked out by other postcolonialists. The book seeks to reveal how Poland's two lines of experience-one of foreign hegemony since the late 1700s through 1989 (excluding a short period of sovereignty between the two world wars); and the other of the Polish-Lithuanian Commonwealth as itself a pre-modern empire-have shaped the culture of contemporary Polish society. The book focuses on identity transformations as reflected in Polish literature and critical discourses. It opens up the question of the identity of a postcolonial nation in contemporary East-Central Europe where globalization and cosmopolitanism clash with growing national sentiments, making predictions about a speedy advent of a post-national era premature. The first few chapters are devoted to the postcolonial theorizing of Poland in the East Central European context. This part of the book seeks relevant language(s) and registers for the analysis of the cultural condition of East Central Europe as a part of the world which slipped most postcolonial critics' attention. The second part of the book (Chapters 7-11) deal with the effects of the colonial encounter on Poles' self-perception and perception of Others, as reflected in Romantic and modern Polish literature. The book closes with a Postscript titled "Three Warnings," outlining a critique of postcolonial theory and criticism"--